(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of the research is to explain the level of community participation in the development of Naga village, Ibu Tenggah, West Halmahera Regency. The study uses qualitative approach methods. The informant is one person as the head of the village, two people as a village officer/device, two as the head of the ward, and five people as the whole society as many as ten Informans. Based on the results of the study showed (1) community participation in decision making related to the development of Naga village, Ibu Tenggah, West Halmahera Regency may still be lacking, some people prefer to give authority Decision making is done by the village apparatus although basically the village head and its ranks to take decisions related to the development of the village adapted to the wishes of the village community related to the development of the village itself however. (2) Community participation in the construction of Naga village, Ibu Tenggah, West Halmahera Regency has been very good, where both people and village governments want to cooperate and mutual cooperation in the implementation of Village development Especially in the development and provision of facilities and infrastructure as well as village Infrastructuretus. In the implementation of government programs also people always participate in it as evidence of their participation both physically and nonphysically. (3) Community participation in the development results of Naga Village, Ibu Tenggah, West Halmahera Regency has been very good. The awareness and sense of responsibility instilled by the village government to the community is extraordinary so that people are able to utilize the results very well to be managed to become potential that can increase the resources People and natural resources around them. People here care deeply and keep the results of their hard work and mutual assistance in development. Each development program and outcome is allocated evenly. (4) Community participation in the evaluation related to the development of Naga village, Ibu Tenggah, West Halmahera Regency has been quite good from the village government to have a meeting every month and each year with the community to listen to the input and of community-related developments. Keywords: Community Participation, Developmen,Village